2013
DOI: 10.1103/physrevd.88.104028
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical bar-mode instability in rotating and magnetized relativistic stars

Abstract: We present three-dimensional simulations of the dynamical bar-mode instability in magnetized and differentially rotating stars in full general relativity. Our focus is on the effects that magnetic fields have on the dynamics and the onset of the instability. In particular, we perform ideal-magnetohydrodynamics simulations of neutron stars that are known to be either stable or unstable against the purely hydrodynamical instability, but to which a poloidal magnetic field in the range of 10 14 -10 16 G is superim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…This value is consistent with the amplitude evolution of the h ¼ 0.15 M ⊙ run, but somewhat smaller than what could be inferred from the h ¼ 0.1 M ⊙ data. However, other physical processes, such as neutrino cooling and angular momentum redistribution due to magnetoturbulence, will likely become dominant over such time scales [22] and might damp the one-armed spiral instability [65][66][67]. As a consequence, our estimate of the survival time of the m ¼ 1 mode should constitute a reasonable upper limit.…”
Section: Hybrid Waveformsmentioning
confidence: 91%
“…This value is consistent with the amplitude evolution of the h ¼ 0.15 M ⊙ run, but somewhat smaller than what could be inferred from the h ¼ 0.1 M ⊙ data. However, other physical processes, such as neutrino cooling and angular momentum redistribution due to magnetoturbulence, will likely become dominant over such time scales [22] and might damp the one-armed spiral instability [65][66][67]. As a consequence, our estimate of the survival time of the m ¼ 1 mode should constitute a reasonable upper limit.…”
Section: Hybrid Waveformsmentioning
confidence: 91%
“…They can only set in when the rotation period is very close to the mass-shedding limit (∼1-10 ms); therefore, they are expected to be suppressed before phase 2 sets in. (ii) Secular instabilities (e.g., r-mode, f-mode instabilities) act on time scales ranging from ∼1 s to several years; they become effective at temperatures T ≲ 10 10 K, typically reached after the first minute of life of the PNS [13][14][15]. In phase 2, the star is too hot (T ≳ 10 11 K) for secular instabilities to be effective (at least, excluding the case of quark stars or stars having exotic matter in the core).…”
Section: Introductionmentioning
confidence: 99%
“…There is clear evidence that it may develop during stellar core-collapse (Ott et al 2005(Ott et al , 2007Scheidegger et al 2008;Kuroda & Umeda 2010) and it has been seen in numerical evolutions of rapidly rotating cold neutron stars (Saijo & Yoshida 2006;Cerdá-Durán et al 2007;Corvino et al 2010). Recently, with the development of magneto-hydrodynamical simulations, the impact of the magnetic field on the dynamical instabilities has been explored (Camarda et al 2009;Franci et al 2013;Muhlberger et al 2014). The results suggest that the bar-mode instability can be suppressed by a very strong magnetic field, B ∼ > 10 16 G. Analytical work, based on a rotating system with cylindrical geometry, has shown that the low T/W instability can be similarly suppressed by a strong toroidal magnetic field B > 10 16 G (Fu & Lai 2011).…”
Section: Introductionmentioning
confidence: 99%